Preschool teacher candidates' pupil control ideology and educational beliefs - Gürşimşek, Işik (My University, 2014)
The aim of the present study was to investigate prospective teacher candidates' educational beliefs and pupil control ideologies. The sample of the study consists of 218 teacher candidate from the early childhood education departments of two Universities at Türkish Republic of North Cyprus (Eastern Mediterranean and International Cyprus). The data was collected by; Parental Modernity Scale, Pupil Control Ideology Form (PCI), and Beliefs about Student Inventory (BSI). Data reveal significant differences on participants' educational beliefs and pupil control ideology due to gender and grade level. Women are seen to have lower scores on traditionalism dimension and less custodial beliefs for pupil control. Participants' modernity scores and humanistic beliefs for pupil control are seen to increase due to grade level. Prospective teachers' traditionalism orientation and beliefs about student were seen to be predictive of their PCI.
Keywords: Classroom management; Early childhood education; Educational beliefs of teachers; Pupil control ideology; Teacher education